THE EFFECT OF SEAWATER SOAKING ON THE STABILITY CHARACTERISTICS OF ASPHALT CONCRETE MIXTURES IN THE COASTAL REGION OF PAPUA: PENGARUH RENDAMAN AIR LAUT TERHADAP KARAKTERISTIK STABILITAS CAMPURAN BETON ASPAL DI WILAYAH PESISIR PAPUA - Dinda Sekar Selni Prawardani (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2025)
This research analyzes the effect of seawater immersion on the performance of asphalt concrete mixtures, using the "Retained Strength Index" as the primary parameter. The background for this research stems from the real-world condition of roads in coastal areas that are frequently submerged in seawater. Seawater, with its salt content, is a factor that can significantly reduce the durability and service life of pavement layers. The objective of this study is to examine the characteristics of asphalt concrete mixtures after exposure to varying durations of seawater immersion and to compare the results with those of freshwater immersion to observe the differences. The research methodology involves a Marshall Test on mixture samples prepared with an optimum asphalt content. The immersion durations applied were 0, 6, 12, 24, and 48 hours, in both seawater and freshwater media. The parameters comprehensively analyzed include Stability, Flow, Density, Marshall Quotient, and the Retained Strength Index. The test results consistently show that the longer the immersion duration, the more the values for stability, flow, and MQ tend to decrease. Specifically, seawater immersion causes a greater reduction in performance compared to freshwater. This decrease in performance is attributed to the salt (NaCl) content in seawater, which gradually erodes the adhesive bond between the asphalt and the aggregates, thereby reducing the overall cohesion of the mixture. Although the RSI value decreases with longer immersion times, the results show that even after 48 hours of immersion, the mixture still meets the minimum specification limit of the 2018 Bina Marga standard, which is 90%. In conclusion, it can be stated that seawater significantly affects the reduction in the strength of asphalt mixtures.